Kurzbericht über die Ausgrabung des kaiser- bis völkerwanderungszeitlichen und wikingerzeitlichen Siedlungsplatzes Hörup LA 28, Kreis Schleswig-Flensburg - Klooss, Ringo (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
In Hörup a settlement of the late Imperial to Migration Period could be documented with houses and fence-parallel structures. Numerous slag pits as remains of bloomery furnaces probably also belong to this epoch. During the Migration Period there is a break-off of the settlement. The next building activities do not begin again until the late 8th and 9th centuries. A settlement continuity from the Migration Period to the Viking Age cannot be proven in Hörup.